Bragg Fibers for Absorption-Based Sensing. (1st April 2015) - Matějec, Vlastimil; Kasik, Ivan; Podrazky, Ondrej; Barton, Ivo
Abstract : Photonic band gap Bragg fibers can be employed for delivery of high powers in medicine, lighting and heating systems, electricity production, and the development of optical sensors of physical and chemical variables. In this paper, results of testing Bragg fibers with hollow cores for pH detection based on absorbance measurements on solutions filled in the cores. Bragg fibers with claddings of three pairs of high- and low-index layers and hollow cores of 70 µ m in diameter were fabricated. Photonic band gap bands of the fibers were estimated theoretically. Aqueous solutions of methyl orange (MO) and hydrochloric acid and bromothymol blue (BTB) in Sörensen buffers were filled into the cores and spectra of MO and BTB were measured for different pH. Calibration curves typical for optical pH sensors were derived from the measured spectra with a reproducibility of about 10%.